Strategi Dakwah Radio BHASA FM dalam Meningkatkan Pemahaman Keagamaan Masyarakat Situbondo - Lubbanatul Widad; Nur Ainiyah (Maddah : Jurnal Komunikasi dan Konseling Islam, 2024)
This article examines Bhasa FM radio's da'wah strategy in increasing the religious understanding of the Situbondo community. Radio has been known for a long time as a medium for conveying information, education and entertainment to the public. However, it is different for Bhasa FM Situbondo radio, a radio whose orientation is not only on these three things but more on the domination of Islamic preaching. Seeing that modern society currently tends to be less interested in religious studies in mosques or prayer rooms, it is hoped that radio can be an alternative in filling and providing religious nutrition for Situbondo Muslims. The research uses field research methods. The researcher looked directly into the field in conducting observations, interviews and documentation studies, to collect complete data and then carry out descriptive analysis to then look for an answer to the focus of this paper. Bhasa FM radio's da'wah strategy uses a sensory da'wah strategy (al-manhaj al-hissy) which is also called an experimental strategy or scientific strategy which is oriented to the five senses and adheres firmly to the results of research and experiments. Bhasa FM Radio invites audiences to join online or off air, apart from that there is also social media such as Twitter, Facebook, YouTube and so on. Apart from that, there is also an external approach, namely data produced by Nielsen surveys, once a month. The aim of this strategy is to find out the age, social and economic status of the listener and all demographic aspects of the listener.